2017
DOI: 10.1016/j.poly.2017.02.039
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, crystal structure, magnetic properties and DFT study of dinuclear Ni(II) complex with the condensation product of 2-quinolinecarboxaldehyde and Girard’s T reagent

Abstract: A dinuclear double end-on azido bridged Ni(II) complex [Ni 2 L 2 (μ-1,1 -N 3 ) 2 (N 3 ) 2 ] (1) with the condensation product of 2-quinolinecarboxaldehyde and trimethylammonium acetohydrazide chloride (Girard's T reagent) (HLCl) has been synthesized and characterized by elemental analysis, IR spectroscopy, single-crystal X-ray diffraction, magnetic measurements and DFT studies. In complex 1 intra-dimer ferromagnetic coupling between Ni 2+ ions (J = +12.0(2) cm -1 ) and inter-dimer antiferromagnetic interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 82 publications
(81 reference statements)
5
27
0
Order By: Relevance
“…However, we can see from the spin density table that there is nearly zero delocalization on Na and bridging Cl atom for all the complexes, and only the significant amount of spin density is showing on the bridging oxygen atoms from phenoxido bridge. Negligible overall spin population on the bridging chloride atoms is the result of partial α and β spin density overlap due to the spin polarization in broken symmetry state ( Figures S8-S10) [36][37][38]. Thus, it may be concluded that the ferromagnetic exchange interactions between two Ni II centers are dominated by phenoxido bridges for all the complexes [39].…”
Section: Theoretical Magnetic Calculationmentioning
confidence: 95%
“…However, we can see from the spin density table that there is nearly zero delocalization on Na and bridging Cl atom for all the complexes, and only the significant amount of spin density is showing on the bridging oxygen atoms from phenoxido bridge. Negligible overall spin population on the bridging chloride atoms is the result of partial α and β spin density overlap due to the spin polarization in broken symmetry state ( Figures S8-S10) [36][37][38]. Thus, it may be concluded that the ferromagnetic exchange interactions between two Ni II centers are dominated by phenoxido bridges for all the complexes [39].…”
Section: Theoretical Magnetic Calculationmentioning
confidence: 95%
“…Among the DFT functionals used, the value of J parameter obtained with the B3LYP* functional is the closest to the experimentally determined figure. The ferromagnetic exchange coupling in complex 18 is determined by overlap of the small magnetically active SOMOs of the metal centers and their minor delocalization towards nitrogen atoms of the bridging azide anions …”
Section: Pseudohalide Metal Complexes With Girard T Reagent Hydrazmentioning
confidence: 99%
“…That review also covers some pseudohalide metal complexes with Girard T reagent hydrazones reported up until 2012 , . In recent years our two research groups (K. Anđelković and co‐workers and I. Turel and co‐workers) have made significant contributions in research into coordination chemistry of pseudohalide metal complexes with Girard T reagent hydrazones . A summary of pseudohalide metal complexes with Girard T reagent hydrazones reported until now is given in Table .…”
Section: Introductionmentioning
confidence: 99%
“…ethan-1-aminium chloride (HLCl). HLCl was synthesized in the reaction of 2-quinolinecarboxaldehyde and Girard's T reagent according to the previously described method [17]. IR (cm (C8), 148.9 (C8a), 167.0 (C10).…”
Section: Synthesis Of (E)-nnn-trimethyl-2-oxo-2-(2-(quinolin-2-ylmementioning
confidence: 99%
“…One part of our research deals with systematic investigation of coordination chemistry, magnetic properties and biological activity of hydrazone metal complexes with pseudohalide ligands. Recently, we systematically investigated pseudohalide complexes of Ni(II) and Zn(II) with the condensation product of 2-quinolinecarboxaldehyde and trimethylammonium acetohydrazide chloride (Girard's T reagent) (HLCl) [17,18]. As a continuation of this research, reactions of Cd(II) with HLCl ligand and pseudohalides (azide, cyanate, thiocyanate) were performed in the present study.…”
Section: Introductionmentioning
confidence: 99%